2012
DOI: 10.3892/or.2012.1919
|View full text |Cite
|
Sign up to set email alerts
|

MRS study of meningeal hemangiopericytoma and edema: A comparison with meningothelial meningioma

Abstract: Intracranial hemangiopericytomas (HPCs) are rare tumors and their radiological appearance resembles that of meningiomas, especially meningothelial meningiomas. To increase the knowledge on the biochemical composition of this type of tumor for better diagnosis and prognosis, we performed a molecular study using ex vivo high resolution magic angle spinning (HR-MAS) magnetic resonance spectroscopy (MRS) perfomed on HPC and peritumoral edematous tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…The glycine and mI contents in Table V show a similar trend compared to other reported studies (43)(44)(45)(46)(47)(48): mI content decreased with astrocytic grade, albeit non-significantly, in agreement with (43)(44)(45)(46)(47)(48). Furthermore, gly content increases with grade, in agreement with previous studies (43,44,46,48) in (43)), and the same trend in gly increase with tumour grade was observed in (47 and 50) (HRMAS studies).…”
Section: Comparison Of Mi/gly Calculated From In Vivo Data and Mi/glysupporting
confidence: 79%
“…The glycine and mI contents in Table V show a similar trend compared to other reported studies (43)(44)(45)(46)(47)(48): mI content decreased with astrocytic grade, albeit non-significantly, in agreement with (43)(44)(45)(46)(47)(48). Furthermore, gly content increases with grade, in agreement with previous studies (43,44,46,48) in (43)), and the same trend in gly increase with tumour grade was observed in (47 and 50) (HRMAS studies).…”
Section: Comparison Of Mi/gly Calculated From In Vivo Data and Mi/glysupporting
confidence: 79%
“…Unlike meningiomas, the level of the glutamine/glutamate complex is not high, alanine is not recognized, a "distinct peak" at 3.8 ppm is absent. Instead, hemangiopericytomas show high peaks at 3.56 ppm, and 3.4 ppm, attributed to myo-inositol/glycine, and glucose, respectively, by some authors [30,31]. However, according to Young-Dae Cho et al [32] these peaks should be classified as resonant frequencies of the "unknown molecule" because; in contrast to myo-inositol and glucose (that have T2 within 110 ms) both of these peaks are observed at long TE [32].…”
Section: Hemangiopericytoma Are Malignant Meningeal Mesenchymal Tumormentioning
confidence: 97%
“…While clinical MR investigations on brain tumors have inspired studies of ex vivo HRMAS MRS of tissue specimens to reveal tumor‐type‐specific metabolic structures and pathways, the most significant value of such ex vivo tissue analyses is in improving interpretation of different tumor types, grades, and progression potential for in vivo MRS. A study of 17 human astrocytomas (four Grade II, one Grade III and 12 Grade IV) has shown spectral similarities between in vivo and ex vivo results (Figure ), and highly significant correlations were found for eight out of the 13 measured metabolite concentrations, including creatine (Cr), glutamate (Glu), glutamine (Gln), myo ‐inositol ( myo ‐Ino), N‐acetylaspartate (NAA), scyllo ‐inositol ( scy ‐Ino), total choline (tCho), glycerophosphocholine (GPC), phosphocholine (PCho), and lipids/macromolecules (Lip/MM) . Similarities between in vivo and ex vivo MRS have also been reported for heterogeneous primary and secondary glioblastomas (GBMs), as well as for hemangiopericytoma and meningiomas, two less heterogeneous tumor types …”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disementioning
confidence: 99%
“…40 In addition to metabolite overlaps, the detection of certain metabolites can also be field strength and sensitivity dependent. For instance, alanine (Ala) was detectable in an HRMAS spectrum at 9.4 T but not at 3 T during in vivo MRS. 31 Despite these technical challenges, the trend of increasing magnetic field strength of clinical MRI scanners means that the clinical translation of HRMAS MRS findings is increasingly possible.…”
mentioning
confidence: 99%